Exploring organisational resilience in context of the lean and agile brand communications agency: a lesson from Cape Town commercial production companies - Taylor-Vermaak, Karen (The IIE, 2016)
This research constitutes an explorative study of organisational and operational characteristics shared by established commercial production companies in Cape Town, and which can be attributed to their organisational resilience and on-going success. It stems from the need for a new approach to advertising that delivers engaging branding messages to an ever demanding and discerning consumer also points to the need for a new agency model. This paper analyses and identifies organisational characteristics shared by Cape Town commercial production companies to which their organisational resilience can be attributed. It is the first of its kind to collect data with which to identify and name the methodologies and conceptual thinking within these organisations, using qualitative and quantitative data collected from executive producers and production company owners as well as the permanent and freelance crew that work with them. The study identifies the management structures, methodologies and conceptual frameworks within these production companies, and relates them to existing documented phenomena that are known to contribute towards organisational resilience, namely agile, lean and Shamrock. It also seeks to question if and how these identified characteristics and business behaviours could be adapted and repurposed in the context of a new model of lean and agile brand communications agency. The findings in this paper serve as a starting point for further research into the development of an improved model of lean and agile branding agency.
Keywords: Brand communication; Organisational resilience